Ghosts of Abu Ghraib - Kennedy, Rory (Nevins, Sheila ; Barrett, Diana, 2006)
Duration: 01:12:00 Wielding startlingly candid interviews with perpetrators, witnesses, and victims, Ghosts of Abu Ghraib provides an inside look at the abuses that occurred at the Iraqi prison in the fall of 2003. Award-winning filmmaker Rory Kennedy explores how, given the right circumstances, typical boys and girls next door can commit atrocious acts of violence.